Social Preferences and Labor Market Policy - Trine Filges; John Kennes; Birthe Larsen; Torben Tranæs (Copenhagen Business School (CBS), Department of Economics, 2006)
We find that the main featues of labor policy across OECD countries can be explained by a simple general equilibrium search model with risk neutral agents and a government that chooses policy to maximize a social welfare function. In equilibrum, policies are chosen to optimal redistribute income from advantaged to disadvantaged workers. A worker can be disadvantaged in the sense that they may have less ability to aquire and utilize skills in the workplace. The model explains why passive benefits tend to fall and active benefits tend to increase during the course of unemployment spell. The model also explains why countries that appear to pursue equity spend more on both active and passive labor market programs.
hdl:10398/7648
Keywords: G10; 330